Enhancing energy efficiency: A case study of lighting retrofit systems in malaysian university environments - Hasan, Md Mahmudul; Ashikujjaman, Md.; Khandaker, Sayma; Norizam, Sulaiman; Hadi, Manap (University of Nis, 2024)
With an enormous potential for demand reduction, lighting is one of the main variables influencing demand of electricity in the building energy industry. In this work, laboratory lighting systems for a Malaysian university are used as a case study to discuss the challenges of designing an efficient lighting system for educational spaces. Experimental results indicate that the university laboratories receive more than 300 lux of light from the present lighting system and natural light during the day, under clear, average, cloudy, and night circumstances, respectively, for instructional purposes. The illuminance requirement is exceeded by the presently installed lighting system. This exceeding illuminance level was discovered to be mostly caused by the excessive amount of installed light. Based on simulation results, it is possible to save a significant amount of energy, money, and greenhouse gas emissions by installing well-arranged light emitting diode (LED) tube lights with a 0.8 maintenance factor.